2014
DOI: 10.1111/evj.12254
|View full text |Cite
|
Sign up to set email alerts
|

Equine grass sickness

Abstract: Equine grass sickness (EGS; equine dysautonomia) is a polyneuronopathy affecting both the central and the peripheral nervous systems of horses. As the name implies, EGS almost exclusively affects grazing horses, resulting in the development of a characteristic array of clinical signs, most of which can be attributed to neuronal degeneration in the autonomic and enteric nervous systems. Varying disease severities occur, largely determined by the extent of neuronal degeneration in the myenteric and submucous ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 126 publications
(222 reference statements)
2
55
0
3
Order By: Relevance
“…This study confirmed anecdotal reports [7,8] that CCG and ileal enteric neurones are not chromatolytic in horses with botulism, in contrast to EGS, suggesting that EGS is unlikely to be caused by the particular BoNTs that caused neuroparalysis in the neuroparalytic botulism horses included here. Since 4 of 5 botulism cases were associated with BoNT/C1 intoxication, these data are inconsistent with the hypothesis that EGS is a toxicoinfection associated with BoNT/C1 producing C. botulinum, unless this toxin has different mechanisms of action when produced in vivo during a toxico-infection rather than following oral toxin exposure.…”
Section: Discussionsupporting
confidence: 92%
“…This study confirmed anecdotal reports [7,8] that CCG and ileal enteric neurones are not chromatolytic in horses with botulism, in contrast to EGS, suggesting that EGS is unlikely to be caused by the particular BoNTs that caused neuroparalysis in the neuroparalytic botulism horses included here. Since 4 of 5 botulism cases were associated with BoNT/C1 intoxication, these data are inconsistent with the hypothesis that EGS is a toxicoinfection associated with BoNT/C1 producing C. botulinum, unless this toxin has different mechanisms of action when produced in vivo during a toxico-infection rather than following oral toxin exposure.…”
Section: Discussionsupporting
confidence: 92%
“…The predominant clinical features of FD are attributable to paralysis of the entire gastrointestinal tract caused by severe enteric neuropathy [3]. Striking similarities in the clinico-pathological features of FD with multiple system neuropathies reported in horses (equine grass sickness; EGS), dogs (canine dysautonomia), hares (leporine dysautonomia), rabbits, alpacas, llamas and sheep (abomasal emptying defect) suggest these represent a specific disease entity with a common aetiology [4]. The authors are unaware of a human neurodegenerative disorder which shares the exquisitely localised neuroanatomic lesions of these animal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…All factors are considered together; a resilient soil-borne agent that, in certain climate conditions, produces a neurotoxin to which the horse may mount an immune response may be a plausible hypothesis. 25 Clinical disease can be classified as acute (<2 days), subacute (2-7 days), or chronic (>7 days). Clinicopathological findings reflect dysfunction of the autonomic nervous system, especially of the gastrointestinal tract.…”
Section: Dysautonomiamentioning
confidence: 99%
“…22), of the myenteric and submucosal ganglia, and, to a lesser extent, from the brain and spinal cord. 25,26 Fig. 22.…”
Section: Dysautonomiamentioning
confidence: 99%